Clinical characteristics of children with lower respiratory tract infections are dependent on the carriage of specific pathogens in the nasopharynx - Tenenbaum, Tobias; Brade, Joachim; Schroten, Horst (European journal of clinical microbiology & infectious diseases, 2012)
A prospective clinical study was performed to correlate nasopharyngeal carriage of bacteria with the type of lower respiratory tract infections (LRTI) in hospitalised children. To determine bacterial load in nasopharyngeal aspirates (NPA) we used semiquantitative culturing and quantitative TaqMan-PCR for those pathogens difficult to culture. Specimens and clinical data were obtained from 311 children between 0 and 16 years of age with LRTI during the period of 2006-2008. The most common detected potentially pathogenic colonisers were Haemophilus influenzae (32.1 %), Moraxella catharralis (26.7 %), Staphylococcus aureus (17.7 %) and Streptococcus pneumoniae (16.7 %). As expected S. aureus was the most common coloniser in children less than 4 months of age, whereas H. influenzae detection peaked in older children. Co-colonisation with other bacterial pathogens were more often observed in children with S. aureus (46 %) and S. pneumoniae (49 %) than in those with H. influenzae (30 %) or M. catharralis (27 %). Children with S. aureus co-colonisation had higher levels of C-reactive-protein, received antibiotics more frequently and stayed longer in hospital than those with S. aureus single colonisation. In contrast, children with H. influenzae, M. catharralis or S. pneumoniae colonisation suffered more often from pneumonia than children with S. aureus colonisation. Coloniser specific analysis of bacterial quantity revealed no significant reduction of the bacterial carriage from the first to the second NPA. No correlation of a high bacterial load and occurrence of pneumonia could be detected. In conclusion, clinical characteristics in children with LRTIs are associated with a specific bacterial set of colonisers detected in the nasopharynx rather than on their quantity.